The Impacts of the Pandemic COVID-19 on Construction Industry in Kuala Lumpur - anaam, ahmed abdulmalek abdulwahab; JUNAIDAH BINTI JAILANI (Recent Trends in Civil Engineering and Built Environment, 2022)
• COVID-19 has affected the construction industry. It has affected all aspects. Most construction projects have stopped, postponed, or slowed down. Many employees and workers have stopped working or lost their work due to the pandemic. This project investigated and evaluated the effects that COVID-19 caused to construction industry by conducting a qualitative study through interviews with contractors in construction companies in Kuala Lumpur, the effects were sorted and analyzed in detail in all aspects. The interview sessions were held through online meetings with 4 contractors in Kuala Lumpur which randomly selected based on contractor listing in Malaysian Construction Industry Development Board (CIDB) website. The results that had impacted building firms due to the global COVID-19 pandemic had been analyzed and evaluated based on thematic content analysis using NVivo software. Results from the interviews found that the MCO has resulted in 6 main impacts consists of (i) time; (ii) cost; (iii) safety; (iv) regulation compliance; (v) limited human resources supplies; and (vi) limited resource availability on-site. These shows that MCO has given the negative impact to the project success. This finding is critical for the government to ensure that they are aware of the MCO’s effects for the construction industry and to assist construction participants in overcoming the six variables identified in this research.